ORP control for boosting ethanol productivity in gas fermentation systems and dynamics of redox cofactor NADH/NAD+ under oxidative stress. Issue 50 (August 2021) - Grimalt-Alemany, Antonio; Etler, Christina; Asimakopoulos, Konstantinos; Skiadas, Ioannis V.; Gavala, Hariklia N.
Graphical abstract: Highlights: Oxidative stress triggers a significant increase in ethanol productivity. Chain elongation is selectively inhibited by oxidative stress. The AOR pathway is involved in the detoxification of reactive oxygen species. The dynamics of NADH/NAD + depend on metabolic activity rate and product ratio. Thermodynamics of the AOR pathway explains the dynamic nature of NADH/NAD + . Abstract: Gas fermentation processes have attracted considerable attention in recent years as they hold high potential for capturing and converting C1 waste gases into a range of biofuels and commodity chemicals. The production of solvents in gas fermentation is typically achieved by exploiting the solventogenic metabolism of acetogenic cultures, which is generally triggered upon exposure to stressful conditions, e.g. low pH. Although the oxidoreduction potential (ORP) is a well-known trigger of the cellular stress response, it has been scarcely investigated as a process control parameter in gas fermentation. Thus, this study focused on evaluating the potential of ORP control strategies for boosting the productivity of ethanol by exploiting the metabolic response to oxidative stress of acetogenic cultures. The dynamics of the redox cofactor pool and ratio as a function of the extracellular ORP and other operational parameters were also studied by monitoring the intracellular levels of the redox cofactor NADH/NAD + . The results showed that increasing the ORP to oxidizing conditions using dilute H2 O2 triggered a 3.7-fold increase in the specific ethanol productivity, from 0.63 ± 0.04 mmol∙gCDW −1 h −1 at an ORP of -210 mV to 2.32 ± 0.19 mmol∙gCDW −1 h −1 at 160 mV. Additionally, the concentration and product selectivity towards ethanol also increased considerably due to the partial inhibition of the chain elongation under oxidative stress. Boost in ethanol productivity and inhibition of the chain elongation were both found to be driven by the presence of H2 O2 rather than by the ORP per se . Studying the profile of the redox cofactors revealed a highly dynamic nature in the pool and ratio of NADH/NAD + as a function of the specific uptake rate and the ratio of acetate-to-ethanol, respectively. The latter was explained by analyzing the thermodynamics of the aldehyde:ferredoxin oxidoreductase (AOR) pathway, which showed that the intrinsic thermodynamic limitation of this pathway imposes a high Fdred /Fdox ratio (>88 % of reduced ferredoxin) while forcing a highly dynamic NADH/NAD + ratio in order to maintain the thermodynamic drive in the forward direction. The dynamics of the NADH/NAD + ratio were also found to be significantly affected by the oxidative stress triggered by dilute H2 O2, which confirmed the involvement of the AOR pathway in the detoxification of reactive oxygen species.